EFFECT OF PLANT GROWTH REGULATORS ON MICROPROPAGATION OF ENDEMIC IRIS STEONPHYLLA HAUSSKN & SIEHE EX BAKER SUBSP. ALLISONII B. MATHEW IN TURKEY - Miric, S. I.; Nasrclar, A. G. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Most geophytes are widely used for pharmaceutical and perfume industry as well as ornamental flowers. Most of them are collected from natural habitats. However, Iris stenophylla Hausskn & Siehe Ex Baker subsp. allisonii B. Mathew is a critically endangered geophyte. Therefore in vitro micropropagation is an important alternative method for the protection and production of this species. We have cultured bulb scale, leaf, skap and immature embryo explants of Iris stenophylla on Murashige-Skoog (MS) media supplementted with various concentrations of plant growth regulators. Immature embryos produced a higher number of bulblets than others. The most bulblets were produced from immature embryos on MS medium supplemented with 1 mg/l BA and 0.25 mg/l NAA. Effective surface sterilization of explants to a level suitable for micropropagation is animportant stage to overcome infection. We report a series of experiments with Iris stenophylla bulbs that involved various concentrations of sodium hypochlorite and HgCl2 treatments of whole bulbs. The best results were obtained from 80% commercial bleach for 20 min. Acknowledgement: This study was supported by the Scientific and Technical Research Council (Project no: TOVAG-105 0 246) of Turkey